Constraints to attracting new hotel workers: A study on industrial recruitment. (January 2017) - McGinley, Sean P.; Hanks, Lydia; Line, Nathaniel D.
Abstract: The global hospitality and tourism industry is not only burdened with high turnover rates but also may soon be in the throes of a labor shortage. As such, a better understanding of industry employment perceptions has become a critical issue for hospitality managers. Of particular concern are the perceptions of those potential employees that do not have prior employment experience in the hospitality industry. Accordingly, the purpose of this research is to consider perceptions of hotel employment among the segment of the potential employee population that has no current or past experience working in hotels. Per the tenets of Constraint Theory, perceptions of pay, promotion opportunities, work-to-life conflict, and workplace-induced isolation are proposed to significantly affect potential employees' attitudes toward hotel employment. In turn, these attitudes are proposed to affect both intention to apply for hotel work and the intention to recommend applying for hotel work to others.